Epidemiology of Prostate Cancer in Saudi Arabia - Abdulghani A. Naeem; Saud A. Abdulsamad; Xi Jin; Gang He; Jiachen Zhang; Qiang Wei; Youqiang Ke (New Frontiers in Medicine and Medical Research Vol. 14, 2021)
Problem identification: Prostate Cancer and its prevalence worldwide have increased over the past several years as the knowledge and methods for early detection of cancer have been improving. Prostate Cancer is also considered to be the second most common cancer in Middle Eastern countries, and is ranked as the sixth leading cause of mortality among men. This study aims to identify the role of genetics and environmental factors in the development and progression of Prostate Cancer among Middle Eastern countries, with focus on the prevalence and mortality of Prostate Cancer in Saudi Arabia. The study also aims to examine proposed risk factors for the development of Prostate Cancer among Middle Eastern men. Literature search: Extensive literature search was made to find articles and studies regarding to the prevalence of Prostate Cancer in Saudi Arabia, and the potential reasons for its increased prevalence over the years. Studies about the established and proposed risk factors contributing to the development of Prostate Cancer was also included in the literature search. Conclusion: Results of literature reviewed and studied in this paper showed that genetics and individual anatomy of Arab men are of importance in the development of Prostate Cancer. For environmental causes, it was identified that the changing lifestyle of Arab men, and becoming more open to Western influence also contributed to the prevalence of Prostate Cancer. It was also found out that with the improving status of the medical practices in Saudi Arabia, it is expected that more cases are to be detected, as more access will be rendered available to the citizens for the immediate detection of Prostate Cancer..